The Effectiveness of the Learning Cycle 5E Learning Model in an Effort to Improve Learning Outcomes of History - Jenny Koce Matitaputty*; Jems Sopacua (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Learning is a process of changing behavior and knowledge. The learning process becomes a system of learning. The results of observations made at SMA Negeri 34 Central Maluku Province of Maluku in history subjects revealed that cognitive learning outcomes in students were still low. One learning model that can train students in solving problems is done by applying the 5E Learning Cycle model. This study aims to analyze the effect of using the 5E Learning Cycle learning model on history learning outcomes at Central Maluku State Senior High School and to analyze the effectiveness of using the 5E Learning Cycle learning model in improving history learning outcomes at Central Maluku State Senior High School 34. This type of research is a pure experiment using a pretest-posttest group design. The samples in this study were students of class XI C as the experimental class and class XI B as the comparison class. The results of data analysis in this study concluded that: (1) the Learning Cycle 5E learning model had an effect on the results of learning history at SMA Negeri 34 Central Maluku; (2) the Learning Cycle 5E learning model is effective in improving history learning outcomes at SMA Negeri 34 Central Maluku.